Pengaruh Karakteristik Ibu Terhadap Pemenuhan ASI Ekslusif Pada Anak 6-23 Bulan - Rismawaty; Isaura Paradise (Kampurui Jurnal Kesehatan Masyarakat, 2020)
This study aims to analyze the influence of social factors (maternal characteristics), economy, and environment on the adequate fulfillment of exclusive breastfeeding in children aged 6-23 months in Indonesia. The analysis was conducted descriptively and inferentially using the Binary Logistic Regression method using data sourced from Susenas in 2017. The results of the analysis showed that the variables of First Marriage Age, education level, and working status of mothers had a significant effect on the fulfillment of adequate exclusive breastfeeding in Indonesia